Distributional Finite-Generalized-Laplace-Hankel-Clifford-Transformation - Gorty, V R Lakshmi (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The distributional finite-generalized-Laplace-Hankel-Clifford transforms is defined and inversion theorem is established in distributional sense. Operational transform formula is obtained for developed finite-generalized-Laplace-Hankel-Clifford transformation. These are applied to solve certain partial differential equations with distributional boundary conditions.